Dietary Iron Supplementation Protects Against Growth Restriction and Metabolic Dysfunction‐Associated Steatotic Liver Disease in Perinatal Cadmium‐Exposed Mice - Rebecca Lichtler; Hannah Klossner; Nikia Smith; Cathrine Hoyo; Michael Cowley (FASEB BioAdvances)
ABSTRACT Iron (Fe)‐deficiency (ID) and Fe‐deficiency anemia (IDA) are highly prevalent conditions and are of particular concern to maternal–child health. ID and IDA are typically linked to nutritional deficiencies, but maternal exposure to heavy metals including cadmium (Cd) also leads to offspring with low levels of circulating Fe. Another comorbidity of ID and IDA is metabolic dysfunction‐associated steatotic liver disease (MASLD), a liver condition characterized by lipid accumulation and fibrosis. We have previously shown that maternal Cd exposure also leads to the development of MASLD in offspring. We hypothesized that providing Fe fortification would prevent Cd‐induced ID, which would in turn rescue offspring from growth restriction and MASLD. To test this, virgin dams were exposed to 30 ppm of cadmium chloride (CdCl2) in their drinking water during the preconception, gestation, and lactation periods. Fe fortification was supplied in the form of dietary ferric citrate, which amounted to two (2×) or five times (5×) the normal dietary Fe in standard chow. Our study provides evidence that perinatal Cd exposure does not prevent absorption of supplemental Fe, and that the chosen Fe supplementation dosages are sufficient to prevent Cd‐induced growth restriction, ID, IDA, and MASLD in offspring at postnatal day 21 (PND21). Our findings suggest that Fe supplementation may be a viable therapy to prevent these developmental effects of maternal Cd exposure.